THE BEHAVIORIAL PHENOMENON OF FRIEND WITH BENEFIT OF ALTER BASE @FWBSMG ON TWITTER - Muhammad Faruq Bukhori (LPPM Institut Pendidikan Nusantara Global, 2023)
The emergence of alter ego accounts on Twitter triggers a new phenomenon called